The Civils the story of the Institution of Civil Engineers - Watson, Garth (Thomas Telford, 1988)
An account of the oldest engineering insitution in the world. It covers the history from the first meetings at the Kendal Coffee House in Fleet Street in 1818 to the acquisition of numbers 1 to 7 Great George Street and beyond.